Scrumban - the Kaban as an addition to Scrum software development method in a Network Organization - Sienkiewicz, Łukasz D. (Scrumban – Kanban jako uzupełnienie metody Scrum używanej do wytwarzania oprogramowania w organizacji sieciowej, 2012)
A large number of press release and scientific publications treat the Scrum as the best approach to software development. Nevertheless, the original Scrum method is not sufficient for managing work in Agile environment within a Network Organization. Due to that, we extended the Scrum-based model [Sienkiewicz, Maciaszek 2011] and the Kanban approach to make the most of both and find a more sufficient approach for managing software development in strongly distributed Agile environment (i.e., Network Organization)
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 2 (24), s. 73-81
Keywords: Scrum; agile; Third Party Service; Network Organization; Scrumban; Kaban; Key Performance Indicators; software development; usługodawcy wewnętrzni i zewnętrzni; organizacja sieciowa; kluczowe wskaźniki wydajności; tworzenie oprogramowania